Wood : Architecture Now! - Jodidio, Philip, 1954- (Cologne : Taschen, 2011)
Wood is renewable and sustainable, solid and attractive. Wood can be bent and shaped to the most modern of designs. It is the material of the moment for contemporary architecture and this new volume allows readers to get a glimpse of the most exciting and dynamic new uses of wood in architecture from all over the world. Like earthen architecture, the use of wood is almost as ancient as building itself. The columns of Greek temples are stylized trees. Today's wooden buildings do all kinds of surprising things, and most of all, they are as "green" as they come. Featured architects and practices include: 70F, A1Architects, AldingerArchitekten, Atelier Masuda, Auer+Weber+Assoziierte, Pieta-Linda Auttila, Shigeru Ban, Beals-Lyon Arquitectos / Christian Beals, Bernardes + Jacobsen, BETON, Bohlin Cywinski Jackson, Enrique Browne, Bernard Bhler, Marco Casagrande, Jos Cruz Ovalle, dECOi Architects, dmvA, dRN Architects, Dumay + Fones + Vergara, Piet Hein Eek, ETH-Studio Monte Rosa / Bearth &
Deplazes, Edouard François, General Design, Seppo Hkli, Yosuke Inoue, IROJE KHM Architects, Jackson Clements Burrows, Emma Johansson and Timo Leivisk, Kauffmann Theilig & Partner, Mathias Klotz, Marcio Kogan, Kirsi Korhonen and Mika Penttinen, Nic Lehoux and Jacqueline Darjes, Niall McLaughlin Architects, Andreas Meck, Beatriz Meyer, Ken Sungjin Min, Murman Arkitekter, Rolf Carl Nimmrichter, Valerio Olgiati, Onix, PUSHAK, Room 11, Hans-Jrg Ruch, SARC Architects, Rodrigo Sheward, Simas and Grinspum, Studio Weave, Tezuka Architects, Turnbull Griffin Haesloop, Wing¥rdhsRecensie : Philip Jodidio heeft weer eens een mooi architectuurboek afgeleverd. Dit nieuwe deel in de reeks 'Architecture Now!' (eerder verschenen onder meer delen over 'Houses' en 'Museums') is een lust voor iedere architectuurliefhebber. Het laat zien dat hout een prachtig materiaal is om fantastische projecten te kunnen realiseren. De architect krijgt steeds meer mogelijkheden met dit milieuvriendelijke materiaal. Het
Boek begint met een inleidend essay en vervolgens passeren 61 projecten van 51 bureaus de revue. Naast Onix, Shigeru Ban en Piet Hein zijn er van vele andere bureaus projecten - ook in Nederland - in dit boek te vinden. Kleurenfoto's van de projecten, geven een goed beeld van de besproken ontwerpen. Het boek is drietalig: Frans, Engels en Duits. Hierdoor is het afzetgebied groter, maar het kan soms ook licht irriterend werken. Het boek leest hierdoor echter wel vlot weg. Een goed overzicht van de hedendaagse houtarchitectuur en de bureaus die daarvoor verantwoordelijk zijn. - Gilbert van der Lee
Keywords: Architectuur; Duurzaam bouwen; Hout; Houtarchitectuur